The usefulness of various subjective and objective measures of circadian phase in sleep medicine diagnostics - Chakrabarty, Mousumi; Lahan, Vivekananda (International Journal of Research in Medical Sciences, 2025)
Circadian rhythm sleep disorders (CRSDs)can be difficult to diagnose as they usually present with a wide array of complaints ranging from insomnia to excessive sleepiness or impairment in the quality of life. Malalignment of the endogenous circadian clock to the external day-night cycle leads to these disorders. There are various subjective and objective methods for assessing these disorders. Both individual subjective and objective measures of circadian phase have their own merits and limitations and a combination of both- especially sleep logs and questionnaires along with actigraphy usually suffice for diagnosing most cases. Dim light melatonin onset (DLMO) and core body temperature (CBT) minimum are also very useful in some cases. Recent advances in the knowledge of neurobiology and genetics of the circadian rhythm should hopefully lead us to improved diagnostic tools and provide us with evidence base practical guidelines for diagnosis and treatment of CRSDs. Circadian Rhythm Sleep Disorders (CRSDs)can be difficult to diagnose as they usually present with a wide array of complaints ranging from insomnia to excessive sleepiness or impairment in the quality of life. Malalignment of the endogenous circadian clock to the external day-night cycle leads to these disorders. There are various subjective and objective methods for assessing these disorders. Both individual subjective and objective measures of circadian phase have their own merits and limitations and a combination of both- especially sleep logs and questionnaires along with actigraphy usually suffice for diagnosing most cases. Dim light melatonin onset(DLMO) and Core body temperature(CBT)minimum are also very useful in some cases. Recent advances in the knowledge of neurobiology and genetics of the circadian rhythm should hopefully lead us to improved diagnostic tools and provide us with evidence base practical guidelines for diagnosis and treatment of CRSDs.